2021
DOI: 10.11591/ijere.v10i1.20823
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous learning in occupational health and safety for vocational education

Abstract: <span>This research aimed to develop instructional media for occupational safety and health android-based for vocational schools. The second aim is to determine the feasibility of instructional media and student responses. The type of research is research and development (R&amp;D) with the Analysis, Design, Development, Implementation, Evaluation (ADDIE) method, namely, analysis, design, development, implementation, and evaluation. The instrument used for data collection was a questionnaire with four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…The validation used in developing digital books is to use media experts and material experts. The material expert shows the suitability assessment and selection of the materials used, while the media expert shows the design assessment from the digital book (Arista & Kuswanto, 2018;Ismara et al, 2021). Based on table 9, it is found that the results are in the good and very good categories, referring to these results it can be concluded that digital books are worthy of trial by considering the suitability of the materials and media used are attractive, creative, and innovative.…”
Section: Resultsmentioning
confidence: 98%
“…The validation used in developing digital books is to use media experts and material experts. The material expert shows the suitability assessment and selection of the materials used, while the media expert shows the design assessment from the digital book (Arista & Kuswanto, 2018;Ismara et al, 2021). Based on table 9, it is found that the results are in the good and very good categories, referring to these results it can be concluded that digital books are worthy of trial by considering the suitability of the materials and media used are attractive, creative, and innovative.…”
Section: Resultsmentioning
confidence: 98%
“…One of the developments in education is the creation of more varied and exciting learning media, thus making the learning atmosphere more conducive and focused (Amali et al, 2020;Indrianto & Kurniawati, 2020). The primary function of learning media is to realize more effective learning (Boyd, 2019;Ismara et al, 2021). It will affect the quality of better learning outcomes if the use of the media is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Menurunnya angka kecelakaan kerja tidak hanya bermanfaat bagi tenaga kerja tetapi akan berimbas terhadap efektifitas pekerjaan sehingga menguntungkan bagi pelaku dunia industri otomotif (Wachter & Yorio, 2014) (Jilcha & Kitaw, 2017). Untuk mengatasi dan meminimalisir resiko kecelakaan kerja, penyelenggra SMK perlu mempersiapkan pelatihan kesehatan dan keselamatan kerja (K3) berbasis industri (Ismara et al, 2021a) (Endroyo et al, 2015) (Wijanarka et al, 2019). Pelatihan K3 dilaksanakan agar calon lulusan SMK dapat mengetahui dan mempersiapkan diri terkait pengetahuan K3 di industri sehingga setelah lulus siswa tidak hanya aman dan mampu bekerja.…”
Section: Pendahuluanunclassified